Pelatihan Manajemen Risiko dan Pendampingan Solusi Hukum bagi UMKM di Kota Bandar Lampung - Idris, Agus Zahron; Suningsih, Sri; Nurdiono , Nurdiono; Septiyanti, Ratna; Waspodo, Lego (Penerbit Goodwood, 2024)
Purpose: This community service activity aims to provide training for MSMEs in Bandar Lampung regarding risk management in business development, business licensing procedures, and IPR registration as well as bridging free legal aid institutions for MSMEs who need legal assistance. Methodology/approach: This community service activity is conducted in the form of training related to legal literacy for MSMEs in Bandar Lampung. Results/findings: The pre-test and post-test showed that the participants' knowledge before socialization was 57%, and increased by 19%, that is, 76%. In this way, partners are more aware of the importance of having a business license and mitigating risks in running a business, as well as other benefits, such as securing legal protection and running business operations safely. In addition, it can make it easier to develop your business, such as collaborating with other business actors, and making it easier to export and import products. Limitation: The limitation of this community service activity is that it looks into the problem faced by MSMEs in Bandar Lampung, which does not have a business license to run the business. Contribution: Partners gain a better understanding of the legal problems and solutions for MSMEs, such as how to make it easier to borrow funds from banks. Other benefits include the provision of business assistance by the government.